BioMaster: An Integrated Database and Analytic Platform to Provide Comprehensive Information About BioBrick Parts - Wang, Beibei; Yang, Huayi; Sun, Jianan; Dou, Chuhao; Huang, Jian; Guo, Feng-Biao (Frontiers in Microbiology, 2021)
Synthetic biology seeks to create new biological parts, devices, and systems, and to reconfigure existing natural biological systems for custom-designed purposes. The standardized BioBrick parts are the foundation of synthetic biology. The incomplete and flawed metadata of BioBrick parts, however, is a major obstacle for designing genetic circuit easily, quickly and accurately. Here, a database termed BioMaster (http://www.biomaster-uestc.cn) was developed to extensively complement information about BioBrick parts, includes 47934 items of BioBrick parts from the iGEM Registry with more comprehensive information integrated from 10 databases, providing corresponding information about functions, activities, interactions and related literature. Moreover, BioMaster is also a user-friendly platform for retrieval and analyses of relevant information on BioBrick parts.